On the issue of educating repatriated children in the Republic of Kazakhstan - Zhilbayev, Zh.O.; Syrymbetova, L.S.; Stanciu, N.; Eskazinova, Zh.A. (Ye.A.Buketov Karaganda State University Publishing house, 2018)
The article is devoted to the study of the peculiarities of teaching children-oralmans in the Republic of Kazakhstan. The authors of the article indicate not only the creation of favorable conditions for the development of the oralmans family as the main motivation for moving to their historical homeland, but also as the abilities of their children in their native cultural environment and further social advancement. The main issues of social adaptation of children-oralmans are revealed. Marked by critical and key learning points oralman children languages. The article reveals the essential concept of «oralman». Experimental results are also presented, which indicate that the second generations of repatriates often use Russian or other languages. The authors focus on the domestic education, which until now was based on the fundamental knowledge in one language, Kazakh or Russian. In conclusion, the authors concluded that the most difficult in the social adaptation of children-oralmans is their inclusion in the education system of Kazakhstan. All states receiving migrants, within the framework of integration programs, first of all attach special importance to language adaptation. That is why, covering the issues of education of children-repatriates, in this article the authors have made a special emphasis on language education.
Қазақстан Республикасында оралман-балаларды оқыту мəселесі
К вопросу обучения детей-репатриантов в Республике Казахстан
Keywords: children-oralmans; adaptation; concept; education; Kazakh language; Russian language; ethnic kazakh; status; state; homeland; oralmans